Optimalisasi Ekonomi Digital dan Lingkungan untuk Pengembangan Masyarakat Berbasis SDGs 8 & 11 - Michael Flaurance Andia, Joey; Soraya, Amanda; Br Ginting, Rahella Ripatiana; Hidayat, Marisca Amanda; Ikaningtyas, Maharani (ABIDUMASY, 2025)
Digital economic development and environmental preservation have emerged as critical components of inclusive and sustainable community growth. The Community Service Program (KKN) held in Kelurahan Wiyung, Surabaya, aimed to explore digital economic potential while promoting eco-conscious behavior in support of SDG 8 and 11. This study applied a descriptive qualitative method, utilizing field observation, semi-structured interviews, and documentation. The core programs included: (1) improving MSME visual identity through the development of a Graphic Standard Manual (GSM), (2) training local women’s groups in the production of eco-friendly soap using soapberries, and (3) enhancing business visibility through Google Maps digitalization. The findings revealed improved community competencies in digital branding, marketing, and sustainable business practices. The high level of participation among community members reflected the effectiveness of the participatory approach. Overall, this program succeeded in not only offering immediate benefits but also fostering long-term digital and environmental awareness among local businesses.